2020
DOI: 10.1186/s12891-020-03634-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective Glenohumeral external rotation deficit – sequelae of post-ORIF deltoid adhesions after treatment of the proximal humerus fracture

Abstract: Background The deltopectoral approach is commonly used for plate stabilization of proximal humerus fracture. Although adhesions between the deltoid, plate, and humerus are common sequelae of plate ORIF, little is known about their effect on the range of movement and a function of the shoulder. To confirm their impact, the preoperative and intraoperative evaluation of the range of motion (ROM) was measured during the sequential arthroscopic release of adhesions, with special regard to external rotation. Postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These results confirm previous studies in which patients with reduced shoulder function after plate osteosynthesis of a proximal humerus fracture had a better functional outcome after implant removal [ 13 , 14 , 21 23 ]. Acklin et al showed that the Constant Score improved significantly from pre- to postoperative in 20 patients with persistent limited range of motion, after elective implant removal at the proximal humerus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results confirm previous studies in which patients with reduced shoulder function after plate osteosynthesis of a proximal humerus fracture had a better functional outcome after implant removal [ 13 , 14 , 21 23 ]. Acklin et al showed that the Constant Score improved significantly from pre- to postoperative in 20 patients with persistent limited range of motion, after elective implant removal at the proximal humerus.…”
Section: Discussionsupporting
confidence: 91%
“…Waszczykowski et al highlighted in their publication that in addition to implant removal, excision of the soft tissue overlying the plates can also be attributed positive effects in postoperative improvement of range of motion. However, no statement is made about implant materials in this study either [ 23 ]. In this previous work, especially external rotation with the humerus at rest was improved by releasing the adhesions over the plate, [ 23 ] whereas the data presented in that manuscript also show an improvement in external rotation with the humerus abducted at 90° for PEEK plates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, contracture of the rotator interval will limit external rotation in adduction; contracture of the antero-inferior capsule will limit external rotation in abduction; and contracture of the posterior capsule will limit internal rotation. Greater limitation of rotation in adduction compared to abduction may be due to extraarticular adhesion around the hardware ( 34 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Osteosynthesis implant removal can be done through an open approach, assisted by an arthroscope or completely arthroscopically. There are several articles demonstrating the feasibility of the removal of a proximal humeral plate arthroscopically ( 2 , 31 , 36 , 37 , 38 ), showing good results without increased complications ( 26 , 34 , 39 , 40 , 41 ). Removal of the plate or nail via an open surgical approach has also shown satisfactory results ( 12 , 28 , 30 ).…”
Section: Treatmentmentioning
confidence: 99%